ADVANTAGES AND YIELDS OF GROWING ONIONS BY SEEDLINGS AND THE NEW METHOD IN THE CONDITIONS OF KARAKALPAKSTAN - Ismoilova N.; Hayitboyev D.; Seilbekov R. (Modern American Journals, 2025)
Methods of sowing onions and their advantages, as well as methods for increasing their yield using new methods.
Keywords: Sowing methods, sowing dates, their effective use, ensuring food security, and improving soil structure.